Workshop: The Future of Work - Lindley, Siân; Raval, Noopur; Alavi, Hamed S.; Lindtner, Silvia; Wang, Ding (CHI'19 Extended Abstracts, 2019)
We invite scholars, designers, developers, policymakers and provocateurs to explore non-standard, global and virtual work futures, to reflect on the impact of new sites and temporal patterns of work, and to consider emerging interpersonal and person-machine dynamics within work. We will frame these discussions with a consideration of the relationship between the future of work and existing modes of labor and political economy, with a view to identifying possibilities for both technological innovation and systemic change.